High-performance devices from surface-conducting thin-film diamond - Jackman, R; Looi, H; Pang, L; Whitfield, MD; Foord, J (Elsevier, 1999)
Early predictions that diamond would be a suitable material for high-performance high-power devices were not supported by the characteristics of diodes and field effect transistors (FETs) fabricated on boron doped (p-type) thin-film material. In this paper commercially accessible polycrystalline thin-film diamond has been turned p-type by the incorporation of near-surface hydrogen, a type of film often referred to as `surface conducting'. Schottky diodes and metal-semiconductor FETs (MESFETs) have been fabricated using this approach which display unprecedented performance levels; diodes with a rectification ratio >106, leakage currents <1 nA, no indication of reverse-bias breakdown at 100 V and an ideality factor of 1.1 have been made. Simple MESFET structures that are capable of withstanding VDS values of 100 V with low leakage and current saturation (pinch-off) characteristics have also been fabricated. Predictions based upon experiments performed on these devices suggest that optimized device structures will be capable of operation at power levels up to 20 W mm-1, implying that thin-film diamond may after all be an interesting material for power applications.